EDUKASI PROSES PENANGANAN PASCAPANEN PRODUK BUAH SEGAR SEBAGAI BAHAN BAKU PEMBUATAN PRODUK OLAHAN - Fatharani, Arina; Yuwana, Yuwana; Sidebang, Bosman (Universitas Mataram, 2025)
The Women's Environmental Care Group (KPPL) of Sumber Jaya and Sejahtera in Rejang Lebong Regency, Bengkulu, faces challenges in post-harvest handling of fresh products, particularly jackfruit and avocado, which serve as the primary raw materials for their processed goods. Without proper handling techniques, the quality of raw materials declines, affecting the quality of processed products. Therefore, training on Appropriate Technology (TTG) for post-harvest handling is needed to enhance the quality of their processed products. The goal of this initiative is to provide KPPL with knowledge on post-harvest handling so that their processed products can be of higher quality and more competitive. The methods include workshops focused on harvesting, storage, transportation, and packaging of fresh products. Training is conducted through hands-on sessions with KPPL members, involving students as activity supporters. Results indicate improved understanding among KPPL members in proper harvesting and storage techniques, which has led to extended shelf life and better quality of fresh products. Overall, the initiative has successfully raised awareness within KPPL on product quality, marketability, and raw material management for processed products. In conclusion, this TTG training has proven effective in enhancing KPPL’s post-harvest handling quality and improving the competitiveness of their processed products in the market.